Dynamics of Sexual Harassment on Social Media - Virgin Suciyanti Maghfiroh1; Faqihul Muqoddam (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
Sexual harassment is a currently netizen’s habit on social media. Almost all of their comments on social media contain words to abuse. This study was conducted with the aim of analyzing the forms of sexual harassment and identifying the factors of sexual harassment on social media. This study uses a qualitative method of narrative tradition with a focus on investigating sexual harassment that occurs on social media. Data collection methods are carried out by observing comments of netizens. The characteristics of the comments that chosen in this study are those written on Instagram and point to the element of sexual harassment. The results show that sexual harassment on social media is happen with; 1. directly (explicitly), 2. indirectly (implicitly) according to the meaning of the sentence. Then, the factors of sexual harassment on social media are; 1. netizens are looking for attention (as evidenced by accounts that are used only fake accounts), 2. photo content or account owner captions that lead netizens to harass. Suggestions based on this study are the need to develop psychoeducation for adolescents and families both as subjects and victims so as to avoid sexual harassment behavior.